Funciones desempeñadas como asistente de finanzas y tesoreria en TAL SA - Castro Ortiz, Lessly Marleni (2018)
The present work has the purpose of showing the work carried out in the agroindustrial company TAL SA as assistant of Treasury and finance. Tal SA is part of the Rocío Group created in March 1967. This organization provides all the support and support for the development of their companies. The synergy that unites companies is based on the recycling of what is produced between them, thus complementing a perfect cycle that benefits the environment and companies. TAL SA company seeks the sustained growth of this and the community working hand in hand with the state and stakeholders, one of the agencies is Enseña Peru. Through programs it seeks to improve the workers of the company, their family and the community in general. It can show the importance of the treasury, manage, retain and pump liquidity through all circuits both internally and through the financial market. Too often, decisions that are constantly taken into account have a direct and irreversible impact on the income statement. Additionally, the financial environment, the current processes of globalization, offshoring, new technologies and banking competition frame the new trends in treasury management. During the stage of university training, I receive part of, the best teachers, as much information as possible as well as the presentation of casuistry that is a near future, development in my work performance.